Retreatability of two hydraulic calcium silicate‐based root canal sealers using rotary instrumentation with supplementary irrigant agitation protocols: a laboratory‐based micro‐computed tomographic analysis. (17th May 2019) - Pedullà, E.; Abiad, R. S.; Conte, G.; Khan, K.; Lazaridis, K.; Rapisarda, E.; Neelakantan, P.
Abstract: Aim: To investigate the retreatability of two calcium silicate‐based materials (BioRoot RCS, Septodont, Saint–Maur‐des‐Fossés, France and GuttaFlow Bioseal, Colténe/Whaledent AG, Langenau, Germany) using rotary instrumentation combined with supplementary irrigant agitation techniques using extracted teeth in a laboratory setting. Methodology: The root canals of extracted single‐rooted mandibular premolars were prepared to size 40, .04 taper and randomly divided into two experimental groups ( n  = 36) depending on the root filling material. Root canals were filled with gutta‐percha and GuttaFlow Bioseal (GB, group 1) or BioRoot RCS (BR, group 2), scanned using a micro‐CT scanner and stored in phosphate‐buffered saline for 4 months. Removal of root filling was performed with rotary instruments, and specimens were randomly allocated to one of the subgroups for supplementary irrigant agitation ( n  = 12): subgroup A, syringe irrigation (control); subgroup B, Tornado Brush (M.I.B, Suresnes, France) and subgroup C, ultrasonically activated irrigation. Specimens were re‐scanned with micro‐CT to calculate the volume of remnant root filling material. Data were analysed statistically by two‐way ANOVA and post hoc Tukey's tests ( P  = 0.05). Results: Specimens filled with GuttaFlow Bioseal were associated with a significantly smaller volume of root filling remnants compared with BioRoot RCS ( P  < 0.05). There was no significant difference between the supplementary irrigant agitation subgroups in the removal of GB ( P  > 0.05). In group 2 (BioRoot RCS), subgroups B (Tornado Brush) and C (ultrasonically activated irrigation) were associated with a significantly smaller volume of root filling remnants compared with subgroup A (syringe irrigation) ( P  < 0.05). There was no significant difference between subgroups B and C ( P  > 0.05). Conclusions: Significantly smaller volumes of root filling remnants of GuttaFlow Bioseal, than BioRoot RCS, were present after their removal with rotary instruments and irrigation. Supplementary irrigant agitation techniques were associated with smaller volumes of remnants during the removal of BioRoot RCS but not that of GuttaFlow Bioseal.